A Run-Time Reconfigurable Ge Field-Effect Transistor With Symmetric On-States - Andreas Fuchsberger; Lukas Wind; Daniele Nazzari; Larissa Kuhberger; Daniel Popp; Johannes Aberl; Enrique Prado Navarrete; Moritz Brehm; Lilian Vogl; Peter Schweizer; Sebastian Lellig; Xavier Maeder; et al. (IEEE Journal of the Electron Devices Society)
Here, we present a Ge based reconfigurable transistor, capable of dynamic run-time switching between n- and p-type operation with enhanced performance compared to state-of-the- art Si devices. Thereto, we have monolithically integrated an ultra-thin epitaxial and defect-free Ge layer on a Si on insulator platform. To evade the commonly observed process variability of Ni-germanides, Al-Si-Ge multi-heterojunction contacts have been employed, providing process stability and the required equal injection capabilities for electrons and holes. Integration into a three top-gate transistor enables effective polarity control and efficient leakage current suppression to limit static power dissipation. Exploiting the advantages of multi-gate transistors, combinational wired-AND gates are shown to be capable of extending a single transistor to a logic gate. Notably, the obtained Al-Si-Ge multi-heterojunction reconfigurable transistors constitute the first CMOS compatible platform to combine efficient polarity control enabling the envisioned performance enhancements of Ge based reconfigurable transistors.